A novel mutation in the UBAP1 gene causing hereditary spastic paraplegia: A case report and overview of the genotype-phenotype correlation - Li, Peiqiang; Huang, Xiande; Chai, Senmao; Zhu, Dalin; Huang, Huirong; Ma, Fengdie; Zhang, Shasha; Xie, Xiaodong (Frontiers in Genetics, 2022)
Hereditary Spastic Paraplegia (HSP) is considered to be one of the common neurodegenerative diseases with marked genetic heterogeneity. Recently, the mutations in ubiquitin-associated protein 1 (UBAP1) have been described in patients with HSP, known as spastic paraplegias 80 (SPG80). We sought to expand the HSP phenotypes and genotypes associated with UBAP1 variants by examining a Chinese family with pure HSP. Their clinical features encompassed spastic paraparetic gait, exaggerated patellar tendon reflexes, bilateral Babinski signs, and Achilles tendon reflex. In addition, the proband had urinary incontinence and a dermoid cyst at the lumbar 4-5 spinal cord, which rarely occurs in HSP patients. Following whole-exome sequencing, a novel heterozygous mutation (c.437dupG, NM_016525) was identified in the UBAP1 that segregated with the family’s phenotype and was predicted to result in loss-of-function of UBAP1 (p.Ser146ArgfsTer13). Moreover, we reviewed the genotypes of UBAP1 and the phenotypic variability in 90 HSP patients reported in the literature. We found that the age of onset in UBAP1-related patients was juvenile, and there were population differences in the age of onset. The main complications were lower extremity spasticity, hyperreflexia, and the Babinski sign. Exon 4 of UBAP1 was identified as a mutation hotspot region. Our study expands the knowledge of UBAP1 mutations, which will aid in HSP patient counseling. Further molecular biological research is needed to explore the genotype-phenotype correlations of UBAP1-related HSP.